The Expatriates Workforce in Malaysia: Challenges of Acculturation Adjustment - Hassan, Sarah Amir (2009)
The following research centers on the expatriates as work force in Malaysia and the challenges of acculturation adjustment. The research reviews challenges encountered by expatriates and psychological and socio-cultural adjustment. A qualitative approach based on semi-structured interviews used to acknowledge the expatiates’ experience in each interview. My objective in this research was mainly to highlight challenges faced by expatriates working in Malaysia, especially in the context of cross-cultural difference and to discover how expatriates coped with these challenges. Core areas were the cross-cultural differences between the West and Malaysia and how the self-adjustment played a key role. Issues like notions of time, recycling, media and remuneration gap were discussed in depth. Findings of the interviews were clearly defined; interpretation of findings comparatively with other studies was illustrated as well. Recommendation from the research findings and conclusions that include suggestions for further studies is the end of the research.